Strategi Segmenting, Targeting, dan Positioning dalam Rangka Percepatan Penurunan Stunting di Provinsi Banten - Shanty Kartika Dewi; Anis Fuad (Universitas Serang Raya, 2022)
Indonesia, as part of the Southeast Asian region, is still experiencing a situation that cannot be separated from the problem of stunting. Every year the prevalence of stunting in Indonesia tends to experience fluctuating conditions. These fluctuating conditions indicate inconsistencies in the implementation of policy programs to reduce stunting. When referring to the WHO maximum stunting prevalence standard of 20%, most provinces in Indonesia have not been able to meet this standard. One of them is Banten Province with a stunting prevalence rate in 2019 reached 24.11%. The conceptualization of the interaction pattern of stunting problems formed from the results of systems thinking is visualized in the form of a causality diagram model. The model, built using the systems dynamics method, serves to provide an understanding of the structural dynamics of the stunting problem, based on the cause-and-effect relationships between the components that make up the problem. This became the basis for the segmenting, targeting, and positioning (STP) strategy planning process. The output of STP strategy planning is compiled into a quality document that is determined according to the level needed to accelerate stunting reduction.